EXAMINING THE ROLE OF THE AMERICAN CORNER IN PROMOTING THE DEVELOPMENT OF ENGLISH LANGUAGE SKILLS AMONG ADULT EFL LEARNERS - Ivanović, Dušan (Metodička teorija i praksa, 2024)
The American Corner serves as a cultural and information center that supports the growth of non-formal adult learning initiatives. This American-style library is particularly important because of the services it provides to English language learners, who visit the Corner regularly in order to hone their language skills. Thus, the aim of this paper is to investigate the role that the Corner plays in promoting the development of English language skills among adult learners through an analysis of relevant theoretical perspectives and empirical studies on English language teaching. The study begins by defining the mission of the American Corner and explaining its role in promoting the importance of non-formal learning programs. Next, the paper examines the effectiveness of the English language programs offered at the Corner by analyzing whether they rely on methods and techniques that are compatible with contemporary approaches to second language acquisition (SLA). The paper concludes by offering some suggestions for future research, which could focus on assessing adult students’ perceptions of their English learning experience within the educational environment provided by the American Corner.
Keywords: American Corner; English language programs; foreign language learning; cooperative learning; TED Talks